PENDAMPINGAN PEMASARAN DIGITAL PADA BUDIDAYA JAMUR TIRAM DI KOMUNITAS MASYARAKAT DESA PANANCANGAN - Noorma Yunia; Budiman; Deden Hidayat; Yayah Rukayah; Maskur (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2025)
Oyster mushroom cultivation (Pleurotus ostreatus) has significant economic potential, given its high nutritional value and growing market demand. However, many farmers face challenges, such as a lack of knowledge and skills in effective cultivation techniques, often relying on inefficient traditional methods. This PKM shows that proper education and training can improve farmers’ skills, thereby increasing crop yields. The application of digital technology, such as in marketing and e-commerce platforms, can help farmers manage cultivation more efficiently and expand market access. Meanwhile, digital marketing systems facilitate online transactions, increasing farmers’ income. Additionally, social media can be used to build communities and raise awareness about local products. Therefore, it is important to develop programs that integrate digital technology into oyster mushroom cultivation to improve efficiency, harvest yields, and farmers’ competitiveness. With the right support, oyster mushroom cultivation can become a sustainable and profitable income source for communities.